Advanced microeconomic theory - Jehle, Geoffrey A.; Reny, Philip J. (England Pearson Education Limited, 2011)
dvanced Microeconomic Theory remains a rigorous, standard in microeconomics, giving all the core mathematics and modern theory the advanced student must master. This student-friendly text, with its efficient theorem-proof organisation, and many examples and exercises, is uniquely effective in advanced courses.